(untitled) (Research, Society and Development, 2020)
This study aimed to assess the quality of surface water at the mouth of the Lucaia River in Salvador (BA), Brazil, through the analysis of physical-chemical and microbiological parameters, considering the influence of low and high tide periods. The values ​​obtained were compared to the standards established by CONAMA Resolution No. 357/05 for freshwater, class 2. The DO concentrations were below the limit required by the Resolution, being the highest in the drought period of 3.3 mg/L in the high tide and the lowest of 0.42 mg/L in the rainy season at high tide. These results corroborate with the BOD values, which were in the range of 166.00 mg/L in the rainy season at low tide and 134 mg/L in the dry season, at low and high tide. In the analysis of thermotolerant coliforms and E. coli values >8 NMP/100mL were found for the rainy and drought periods, both at low tide and at high tide. The IQA classified surface waters as bad at low tide during the rainy season and at high tide during the dry season. However, it was classified as regular at low tide during the dry season and at high tide during the rainy season. The EIT classified surface waters as ultraoligotrophic at low tide and as oligotrophic at high tide in the rainy season. For the dry season, the waters were classified as ultraoligotrophic at low and high tides. The PCA confirmed the high variability of the data, temporal influence and tidal regimes evaluated on the analyzed parameters.